Space Climate and Solar Energetic Particles - Ehsan Tavabi; Sima Zeighami; Yones Kharaghani (Iranian Journal of Astronomy and Astrophysics)
In this paper, we investigate the effect of solar corona magnetic activities during 11-year periods and energetic particles on global warming. According to atmospheric changes during the past years, the relationship between these two issues should be investigated. How the activities of the solar corona affect the average temperature of the Earth and also the increase in its temperature, have been the attention of researchers in recent years. For this purpose, we use the source of data recorded from the momentary position of the Sun in reliable sites, as well as information recorded from the flow of cosmic particles on the surface of the Earth by the GOES (Geostationary Operational Environmental Satellite) detector, which belongs to the NASA space agency. Solar activity affects the Earth's geomagnetic field and creates a geoelectric field on the Earth's surface. This phenomenon can affect technological systems, such as power grids, oil and gas pipelines, and railway systems, leading to damage to power grids, equipment, line breaks, and even blackouts. Results of this study show that there is a significant relationship between the magnetic activities of the Sun in 11-year cycles and the temperature of the Earth, which can be considered an essential parameter in predicting many crises and climate changes on the Earth's surface. Our results also indicated that changes in the number of sunspots and cosmic particles are inversely to each other.